PENINGKATAN HASIL BELAJAR KELIPATAN PERSEKUTUAN TERKECIL (KPK) DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK DI KELAS IV SD - Nasution, Murniza (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Background research by the low student learning outcomes in multiple learning smallest union in the fourth grade of SD N 04 Gunung Tuleh in West Pasaman. This occurs because in learning to teach mathematics multiples smallest union in the traditional way with the meaning of the word is not linked with real life learning students. One approach to learning can improve learning outcomes is Realistic Mathematics Approach. The results of the research that has been conducted every cycle saw an increase in students' first cycle with the results of the meeting I RPP 79%, meeting the first of cycle II increased to 82.41%, while on the second cycle to be 92.85%. Activities teachers on learning KPK with PMR cycle I of meeting I was 71.42%, in the first cycle of meeting II increased to 75%, while the second cycle to be 92.85%. Activity students in learning KPK with PMR first cycle of meetings I was 60.71%, the percentage of completeness 56.00%, the first meeting of cycle II increased to 71.42%, the percentage of completeness 68.67%, while the second cycle to be 89.28%, the percentage of completeness 85.33% . Based on observations made also saw an increase in activity in the learning process. So it can be concluded that PMR approach can improve student learning outcomes in learning KPK in the fourth grade of SD N 04 Gunung Tuleh in West Pasaman.   Keywords:      learning outcomes, multiples guild smallest, realistic mathematics education approach